2012
DOI: 10.1042/bj20111770
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic measurements of mitochondrial hydrogen peroxide concentration and glutathione redox state in rat pancreatic β-cells using ratiometric fluorescent proteins: confounding effects of pH with HyPer but not roGFP1

Abstract: Using the ROS (reactive oxygen species)-sensitive fluorescent dyes dichlorodihydrofluorescein and dihydroethidine, previous studies yielded opposite results about the glucose regulation of oxidative stress in insulin-secreting pancreatic β-cells. In the present paper, we used the ratiometric fluorescent proteins HyPer and roGFP1 (redox-sensitive green fluorescent protein 1) targeted to mitochondria [mt-HyPer (mitochondrial HyPer)/mt-roGFP1 (mitochondrial roGFP1)] to monitor glucose-induced changes in mitochond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 38 publications
3
55
0
3
Order By: Relevance
“…Using this probe, we found that lowering the glucose concentration from 10 to 5 mmol/l for 18 h increases thiol oxidation in the mitochondrial matrix of dispersed rat islet cells. The increase in mt-roGFP1 fluorescence ratio in G5 is unlikely to have resulted from reduced expression of glutaredoxin without changes in thiol oxidation state, as it also occurs upon acute reduction of glucose from 10 to 2 mmol/l [19]. The increase in mt-roGFP1 fluorescence ratio may also have resulted from a decrease in mitochondrial glutathione content without changes in mt-roGFP1 oxidation state, but we consider this hypothesis unlikely because islet total glutathione content increased [27] and the mitochondrial and cytosolic concentrations of GSH are similar in other cell types (reviewed by Lash [32]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using this probe, we found that lowering the glucose concentration from 10 to 5 mmol/l for 18 h increases thiol oxidation in the mitochondrial matrix of dispersed rat islet cells. The increase in mt-roGFP1 fluorescence ratio in G5 is unlikely to have resulted from reduced expression of glutaredoxin without changes in thiol oxidation state, as it also occurs upon acute reduction of glucose from 10 to 2 mmol/l [19]. The increase in mt-roGFP1 fluorescence ratio may also have resulted from a decrease in mitochondrial glutathione content without changes in mt-roGFP1 oxidation state, but we consider this hypothesis unlikely because islet total glutathione content increased [27] and the mitochondrial and cytosolic concentrations of GSH are similar in other cell types (reviewed by Lash [32]).…”
Section: Discussionmentioning
confidence: 99%
“…Adenoviruses Adenoviruses encoding redox-sensitive green fluorescent protein (roGFP1) and mitochondria-targeted mtroGFP1 were generated and amplified using the pAdEasy system (Stratagene, La Jolla, CA, USA), as described (electronic supplementary material [ESM] Methods) [19].…”
Section: Methodsmentioning
confidence: 99%
“…In addition to metabolic genes, physiological glucose stimulation improves and maintains the β-cell differentiated phenotype by modulating several stress responses and prosurvival/proapototic effectors and pathways (Van de Casteele et al 2003, Martens et al 2005, Hou et al 2008a, Bensellam et al 2009, Roma et al 2012, Sarre et al 2012. Among them, the UPR occupies a central place (Elouil et al 2007, Bensellam et al 2009).…”
Section: Figurementioning
confidence: 99%
“…Wolf et al (14) developed mitochondria-targeted roGFP for assessing changes of redox state, which has been used in Drosophila (15). Two other reporter genes, HyPer and mt-cpYFP, have also been developed to detect H 2 O 2 and superoxide in mitochondria, respectively (16,17). These reagents are extremely useful for real-time measurement in cultured cells as they report instant changes in ROS production and redox state, but cannot be readily used for in vivo measurements because the readouts change instantaneously.…”
mentioning
confidence: 99%